2011
DOI: 10.1002/cne.22692
|View full text |Cite
|
Sign up to set email alerts
|

A‐kinase anchoring protein 150 expression in a specific subset of TRPV1‐ and CaV1.2‐positive nociceptive rat dorsal root ganglion neurons

Abstract: Modulation of phosphorylation states of ion channels is a critical step in the development of hyperalgesia during inflammation. Modulatory enhancement of channel activity may increase neuronal excitability and affect downstream targets such as gene transcription. The specificity required for such regulation of ion channels quickly occurs via targeting of protein kinases and phosphatases by the scaffolding A-kinase anchoring protein 79/150 (AKAP79/150). AKAP79/150 has been implicated in inflammatory pain by tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 100 publications
1
30
2
Order By: Relevance
“…In sensory neurons, TRPV1 cation channels excite neurons in response to heat, acidity or chemical ligands, initiating nociception (Caterina et al, 1997; Zheng, 2013). AKAP79/150 (human/rodent) recruits PKA, PKC, calcineurin (CaN), receptors and possibly transcription factors to organize signaling complexes centered on these three types of channels (Brandao et al, 2012; Chaudhury et al, 2011; Gomez et al, 2002; Hoshi et al, 2005; Kosenko et al, 2012; Tunquist et al, 2008). However, optical observation of individual AKAP79/150 protein complexes (<100 nm) with these proteins has not been achieved due to the intrinsic diffraction limit of light (~250 nm).…”
Section: Introductionmentioning
confidence: 99%
“…In sensory neurons, TRPV1 cation channels excite neurons in response to heat, acidity or chemical ligands, initiating nociception (Caterina et al, 1997; Zheng, 2013). AKAP79/150 (human/rodent) recruits PKA, PKC, calcineurin (CaN), receptors and possibly transcription factors to organize signaling complexes centered on these three types of channels (Brandao et al, 2012; Chaudhury et al, 2011; Gomez et al, 2002; Hoshi et al, 2005; Kosenko et al, 2012; Tunquist et al, 2008). However, optical observation of individual AKAP79/150 protein complexes (<100 nm) with these proteins has not been achieved due to the intrinsic diffraction limit of light (~250 nm).…”
Section: Introductionmentioning
confidence: 99%
“…It therefore has an important role in the regulation of TRPV1 phosphorylation, and functionally the interaction between TRPV1 and AKAP79/150 is required for TRPV1 sensitisation or recovery from desensitisation. AKAP79/150 is expressed in 70-90 % of TRPV1-positive DRG neuron (Schnizler et al 2008;Zhang et al 2008;Brandao et al 2012), and co-precipitation studies have demonstrated a direct interaction between AKAP79/ 150 and TRPV1 (Schnizler et al 2008;Zhang et al 2008). …”
mentioning
confidence: 97%
“…AKAP79 has been shown to interact with several other receptors and channels, such as the ␤2-adrenergic receptor, KCNQ2 channels, AMPA and NMDA receptors, and L-type voltage-gated Ca 2ϩ channels (for review, see Beene and Scott, 2007). The interaction of AKAP79 with AMPA and NMDA glutamate receptors has become an important topic of investigation in synaptic plasticity involved in memory and learning.…”
Section: Discussionmentioning
confidence: 99%
“…AKAP79 has also been shown to mediate the basal phosphorylation and dephosphorylation of AMPA GluR1 receptors in a process thought to underlie long-term depression (Tavalin et al, 2002). Moreover, activation of NMDA receptors can regulate the synaptic localization of AKAP79 through activation of calmodulin and remodeling of F-actin (Gomez et al, 2002) and can regulate AMPA receptor endocytosis through the interaction of AKAP79 and the postsynaptic density protein 95 (Bhattacharyya et al, 2009). More recently, it has been shown that NMDA receptor activation in trigeminal sensory neurons modulates AKAP150/ 79-mediated phosphorylation of TRPV1 by PKA and PKC (Lee et al, 2012), suggesting that TRPV1, NMDA receptor, and AKAP150/79 form a signaling complex that could be involved in the underlying sensitization of sensory neurons in inflammatory and neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%